Impacto de la innovación sobre el rendimiento de la MIPYME: un estudio empírico en Colombia (2012)
The objective of this article is to provide an empirical verification of the existing relationship between the degree of innovation of a company and its performance. To this end, a study was carried out which involved 60 medium and high technology mSMEs in Cali, Colombia. The results of the study show that innovation in products and processes has a positive influence on the performance of the mSMEs. These results not only reinforce the claim that innovation can not only be a sustainable competitive advantage, but can also be useful to make entrepreneurs aware of the need to innovate in order to improve competitiveness, and to help public administration officials in their role as promoters of innovation through financial and non-financial assistance programs.